2014
DOI: 10.1002/cbic.201402135
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Native and Protease‐Resistant Ubiquitylated Peptides

Abstract: The reversible post-translational modification (PTM) of eukaryotic proteins by ubiquitin (Ub) regulates key cellular processes including protein degradation and gene transcription. Studies of the mechanistic roles for protein ubiquitylation require quantities of homogenously modified substrates that are typically inaccessible from natural sources or by enzymatic ubiquitylation in vitro. Therefore, we developed a facile and scalable methodology for site-specific chemical ubiquitylation. Our semisynthetic strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…To validate these results, we used a Bio-Layer Interferometry-based direct binding assay to compare the binding of a substrate mimetic to a USP12 active site mutant (C48S) with or without the two activators. In these assays, we replaced Ub-AMC with a Ub-peptide conjugate, Ub~(AKA), which contains a natural Ub-lysine iso-peptide linkage imitating the physiological substrates of USP12 (Weller et al, 2014). In agreement with our enzyme kinetics data, our binding studies revealed negligible changes in the substrate binding affinity of USP12 induced by UAF1 or WDR20 (Figure 6A and S6).…”
Section: Resultsmentioning
confidence: 99%
“…To validate these results, we used a Bio-Layer Interferometry-based direct binding assay to compare the binding of a substrate mimetic to a USP12 active site mutant (C48S) with or without the two activators. In these assays, we replaced Ub-AMC with a Ub-peptide conjugate, Ub~(AKA), which contains a natural Ub-lysine iso-peptide linkage imitating the physiological substrates of USP12 (Weller et al, 2014). In agreement with our enzyme kinetics data, our binding studies revealed negligible changes in the substrate binding affinity of USP12 induced by UAF1 or WDR20 (Figure 6A and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chatterjee et al reported an auxiliary-mediated ubiquitination method employing 2-mercaptoethoxyl group as the auxiliary [16]. The 2-mercaptoethoxyl auxiliary was introduced to the α-amine of Gly76 which had been attached to the lysine side chain during SPPS.…”
Section: Chemical Methods For Protein Ubiquitinationmentioning
confidence: 99%
“…Chief among those that afford native isopeptide linkages are native chemical ligation (NCL) and expressed chemical ligation (EPL). Both NCL and EPL utilize temporary auxiliaries to facilitate chemical ligation with a Ub C-terminal thioester (Figure 2A) [16-18]. The auxiliaries are typically removed under reducing conditions to furnish a native linkage.…”
Section: Synthesis Of Defined Ub-substrate Conjugates — An Overviewmentioning
confidence: 99%